Deposition of Nanostructured Fluorine‐Doped Hydroxyapatite Coating from Aqueous Dispersion by Suspension Plasma Spray. Issue 9 (2nd August 2016) - Liu, Guanxiong; Geng, Xin; Pang, Huan; Li, Xinran; Li, Xiaotian; Zhu, Peizhi; Zhang, Chao
Abstract : In this study, we prepared an aqueous dispersion of fluorine‐doped hydroxyapatite (FHA) nanoparticles by a wet chemical method. For the first time, the as‐prepared aqueous dispersion of FHA nanoparticles was directly used as suspension for depositing nanostructured FHA coating on stainless steel substrate by suspension plasma spray (SPS) method. Field‐emission scanning electron microscopy images confirm that the coating was nanostructured. X‐ray Diffraction pattern, Fourier‐transform infrared spectroscopy, and Raman spectra show that the as‐sprayed coating was FHA phases. The experimental result confirmed that OH − and F − ions have been well kept in FHA crystal lattice and structural integrity has been maintained during SPS process by using an aqueous dispersion of FHA nanoparticles. The potentiodynamic polarization and electrochemical impedance spectroscopy results prove that the nanostructured FHA coating can greatly enhance the anticorrosion performance of stainless steel in phosphate‐buffered saline solution.